A case of Langerhans' cell histiocytosis of the mandibular condyle - IKEHATA, Masahiro; MATSUDA, Mitsuyoshi; YOSHIDA, Masatsugu; FUJIMORI, Masaki; SHIMAZU, Shinji; TANI, Kazutoshi (Japanese Journal of Oral and Maxillofacial Surgery, 2008)
This report describes a 42-year-old man with Langerhans' cell histiocytosis of the mandibular condyle. The patient was referred to our hospital in 2005 for a further evaluation of pain in the left temporomandibular joint (TMJ) on mouth opening. This symptom was noted by his general practitioner. The patient was prescribed an analgesic treatment because a temporomandibular disorder was suspected on the basis of his symptoms at presentation. However, the treatment had no effect on his symptoms. Computed tomography a month after presentation showed a region of bone resorption in the left mandibular condyle. Fine needle aspiration biopsy did not lead to a diagnosis. Subsequently, open biopsy yielded a diagnosis of Langerhans' cell histiocytosis. Two years two months after presentation, there is no evidence of recurrence.